El endemismo en la flora fanerogámica mexicana: una apreciación analítica preliminar - Rzedowski, Jerzy (Instituto de Ecología, A.C., 1991)
This contribution is essentially a complement to the data and concepts exposed in a previous paper, devoted to the topic of  diversity and origins of the Mexican phanerogamic flora. A part  of the mentioned paper deais with the subject of endemism  which, according to evidence and estimations, involves the  family level and accounts for *10% of the genera and *52% of  known species. If an ecologically more natural area (wich expands the territory of México by about 1/3) is taken as  reference, these figures rise respectively to *17% and *72%. If these figures are compared with existing information for other countries and regions of the world, it can be concluded  that the extent of endemism in the flora of México is not as  iarge as that of Australia, Madagascar or South Africa, but  surpasses that of Cuba and of the California floristic province  and is much iarger than those of many other parís of the world. The origin of this significant wealth of endemic organisms must be sought on the one hand in the existence of a fair number of  regions that behave as true ecological islands and penínsulas  within the territory of México, some of them extending over  Iarge portions of the country, and on the other hand, in the  events and environmentai conditions of the geological past.  Particularly, it must be emphasized that during much of the  Cenozoic era no terrestrial connection existed with South  America and accordingly México bore the form of a península  which, much like South Africa, penetrated in form of a wedge  toward ciimatic conditions in Sharp contrast with those  revailing on the wider part of the continent. Different types and  aspects of endemism in Mexican flora are discussed and it is  pointed out that an important proportion of very local and/or  rare species can be recognized. The majority of endemics, however, do not belong to this group and in fact many of the  most common and characteristic plants of the Mexican  landscape belong to taxa of restricted distribution, including a  Iarge number of weeds and some cultivars. Gypsophytes stand out among edaphic endemics and this  roup seems to bear a long evolutionary history. A largó additional  assemblage of paleoendemics can be distinguished, in part  concentrated in areas which acted as refugia during the epochs  of changing climates of the Tertiary and the Quaternary. A  rough estimation indicates that endemism in the Mexican flora  is most accentuated among shrubs and perennial terrestrial  herbs, whereas lianas and aquatic plants show the lowest  incidence. Among the Iarger families, Cactaceae, Rubiaceae and Compositae stand out with about 70% of endemic species, while Orchidaceae and Gramineae only revea! 35% and 25%  respectively.A remarkable correlation can be observed between the  proportion of endemic genera and the degree of ciimatic aridity. At the species ievel, however, températe and semí-humid areas are equally privileged in endemics. On the other  hand in warm and humid regions endemism is poorly  represented. Numbers of localities and regions are indicated, in which a  significant concentraron of floristic endemism has been  detecíed and in general terms it can be observed that endemic  genera are much better representad in the northern haif of the  country, whereas endemic species are more numerous on the  Pacific slopes iban on the Atlantic. It is pointed out, however,  that in most parts of the country, practically at any point, the  flora of terrestrial and not excessively disturbed communities  inciudes a high percentage of endemics.